2000
DOI: 10.1128/jb.182.3.789-795.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Extradiol Dioxygenase Involved in Tetralin Biodegradation: Gene Sequence Analysis and Purification and Characterization of the Gene Product

Abstract: A genomic region involved in tetralin biodegradation was recently identified in Sphingomonas strain TFA. We have cloned and sequenced from this region a gene designated thnC, which codes for an extradiol dioxygenase required for tetralin utilization. Comparison to similar sequences allowed us to define a subfamily of 1,2-dihydroxynaphthalene extradiol dioxygenases, which comprises two clearly different groups, and to show that ThnC clusters within group 2 of this subfamily. 1,2-Dihydroxy-5,6,7,8-tetrahydronaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…The dominant OTU 72 in Bulk-1200 soil (69 clones in both replicates) was placed in the ThnC cluster named according to the thnC gene from Sphingopyxis macrogoltabida TFA strain. The ThnC enzyme catalyses the ring cleavage of tetralin, an aromatic compound composed of one aromatic ring structure fused to a six-carbon aliphatic ring structure (Andujar et al, 2000).…”
Section: In Silico Hhai Fragmentsmentioning
confidence: 99%
“…The dominant OTU 72 in Bulk-1200 soil (69 clones in both replicates) was placed in the ThnC cluster named according to the thnC gene from Sphingopyxis macrogoltabida TFA strain. The ThnC enzyme catalyses the ring cleavage of tetralin, an aromatic compound composed of one aromatic ring structure fused to a six-carbon aliphatic ring structure (Andujar et al, 2000).…”
Section: In Silico Hhai Fragmentsmentioning
confidence: 99%
“…Physical and genetic analysis of mutants led to the identification of a genomic region involved in tetralin biodegradation which comprises two divergent operons (22). Identification of thnC, coding for an extradiol dioxygenase, and characterization of the reaction catalyzed by its gene product indicated that biodegradation of tetralin by strain TFA also involves an initial metabolization of the aromatic ring by a meta-cleavage catabolic pathway (2). However, a complete biodegradation pathway has not yet been established.…”
mentioning
confidence: 99%
“…Catechol, 3-methylcatechol, 4-methylcatechol, and 2,3-dihydroxybiphenyl were purchased from Aldrich at the highest purity available. The corresponding ring fission products were synthesized biologically by whole cells of NCM631/ pIZ227,pIZ591, which overproduce the broad-substrate-specificity extradiol dioxygenase ThnC (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations